The Analysis of the Implementation of the Storytelling Method on Students' Speaking Skills in Indonesian Language Subject for Fourth Grade at MI Al Adli Palembang - Ayu Apriana; Mardiah Astuti; Siti Fatimah; Al Ihwanah; Ines Tasya Jadidah (The Future of Education Journal, 2025)
This study examines global challenges in enhancing elementary school students' speaking skills with a focus on the effective implementation of the storytelling method. The aim of the research is to analyze the implementation of storytelling to improve speaking skills and identify obstacles encountered during the learning process. A qualitative descriptive approach was used, with subjects consisting of teachers and fourth-grade students at MI Al Adli Palembang. Data were collected through observations, interviews, and documentation, and analyzed using data reduction, data presentation, and conclusion drawing. The results indicate that the systematic application of the storytelling method through stages of planning, implementation, and evaluation effectively improved students' speaking competence, enthusiasm, and self-confidence, despite challenges related to language and classroom management. The conclusion affirms storytelling as a valuable pedagogical approach that requires adaptive teaching strategies and a supportive learning environment to optimize its benefits in Indonesian language learning.